Inflation Targets Regime and global financial cycle: An assessment for the Brazilian economy - Araujo, Elisangela Luzia; Araujo, Eliane Cristina de; Fonseca, Mateus Ramalho da; Silva, Pedro Perfeito da (PSL Quarterly Review, 2020)
In light of the global financial cycle (GFC), this paper investigates the effectiveness of monetary policy in Brazil since the adoption of the inflation targeting regime. The theoretical section analyses monetary policy from the New Macroeconomic Consensus perspective, emphasizing the implications of the GFC. It also contrasts central bank theory with the post-Keynesian critique. For the empirical investigation, a Markov-switching vector autoregressive model is estimated from January 2000 to December 2017, combining the common variables from the empirical literature with the proxy for the GFC. The main results suggest that greater financial instability has a direct effect on domestic inflation. JEL codes:C14, E12, E42